Structural Bioinformatics: An Algorithmic Approach - Forbes J Burkowski (Chapman and Hall/CRC mathematical & computational biology series., 2009)
The Beauty of Protein Structures and the Mathematics behind Structural BioinformaticsProviding the framework for a one-semester undergraduate course, Structural Bioinformatics: An Algorithmic Approach shows how to apply key algorithms to solve problems related to macromolecular structure.